PARENT’S READINESS TO IMPLEMENTATION OFFLINE LEARNING IN PROBOLINGGO - Yudha Muhammad; Musthika Qida Mashithah; Tien Aminah (Indonesian Journal Of Empirical Nursing Sciences, 2024)
Since covid- 19 condition in Indonesia, the goverment has encouraged implementation of limited offline learning as a step to restore lost competencies during online learning period. Offline learning in the middle of a pandemic makes parent that their children necessary to achieve maximum educational goals. The aim of this study are parent’s readiness to implementation offline learning. The design of this study used descriptive study. The population of study are 68 parent. The sampling technique used purposive sampling. The sample is 42 children, collected data used questionnaire sheet. The research site is in SDN Kanigaran 03 Probolinggo, East Jawa, Indonesia in June- July 2023. The result of study showed that almost half of the respondent, readiness of parent in offline learning 48% ready, 28% well readiness, and 24% less readiness. The sample of this study 58 respondent and used total sampling. Instrument of this variable used questionnaire. An overview of the degree of fall risk in older adults with hypertension is the variable under study. Based on this research, it can motivate elderly, to better maintain their diet and always maintain safety and health. Risk of fall eldery with hypertension can be decreased with preventive measures that can be given to the eldery.